Achievement motivation and mental health among medical postgraduates: the chain mediating effect of self-esteem and perceived stress - Ma, Mu-yun; Li, Yao; Guo, Li; Yang, Guan-e (Frontiers in Psychology, 2024)
Medical postgraduates generally experience high levels of depression and anxiety. Previous studies have investigated the impact of various achievement motivations on depression/anxiety among medical students. This study focused on self-esteem and perceived stress, examining the internal mechanisms through which achievement motivation affects depression/anxiety. 530 medical postgraduate students (66.04% female and 33.96% male) were administered the Achievement Goal Orientation Scale, Self-Esteem Scale, Perceived Stress Scale, and Depression-Anxiety-Stress Scale. Results indicated that: (1) Mastery-approach goals were negatively correlated with depression/anxiety; Mastery-avoidance goals were positively correlated with depression/anxiety; Performance-avoidance goals positively predicted depression/anxiety;(2)Self-esteem mediated the relationship between achievement motivation and depression/anxiety;(3)Perceived stress played a mediating role in the relationship between achievement motivation and depression/anxiety; (4) Self-esteem and perceived stress played a chain mediating role in the relationship between achievement motivation and depression/anxiety; (5) There was no significant linear correlation between mastery-approach goals and depression/anxiety. The cross-sectional design was adopted in the present study. The measurement of self-report scales was influenced by the social approval effect. The research findings reveal a mediating pathway between achievement goals and mental health, offering new insights into mental health education for medical graduate students.